2007
DOI: 10.1097/dad.0b013e318053db45
|View full text |Cite
|
Sign up to set email alerts
|

Giant Pilomatricoma

Abstract: A 52-year-old man was examined for an ulcerated, rapidly growing reddish nodule. It was 5.5 cm high with an 11 x 6-cm base and located on the left clavicle. The lesion had been present for approximately 7 years, and the patient complained occasional burning and pain. Clinical differential diagnoses included cutaneous lymphoma, sarcoma, squamous cell carcinoma, and cutaneous metastasis. Histopathologic examination revealed a well-circumscribed tumor involving the whole dermis and the subcutis and composed of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 18 publications
0
39
0
Order By: Relevance
“…The examination also showed extensive calcium deposits and multinucleated giant cells foreign-body type. 3 Kaddu et al 17 reported that the early PM fully developed can be distinguished by histopathologic analysis, demonstrating that there is a chronological evolution of the PM lesion from an infundibular matrix cyst to a calcified and ossified dermal nodule.…”
Section: Cells With Shadows Of Lost Nuclei and Clear Intercellular LImentioning
confidence: 99%
See 2 more Smart Citations
“…The examination also showed extensive calcium deposits and multinucleated giant cells foreign-body type. 3 Kaddu et al 17 reported that the early PM fully developed can be distinguished by histopathologic analysis, demonstrating that there is a chronological evolution of the PM lesion from an infundibular matrix cyst to a calcified and ossified dermal nodule.…”
Section: Cells With Shadows Of Lost Nuclei and Clear Intercellular LImentioning
confidence: 99%
“…Pain and tenderness may be associated symptoms. 3,5 The tumor is generally observed on the head, neck and upper extremities. 6 It is a common skin neoplasm in the pediatric population, but it may be found in all age groups with bimodal peaks under the age of 30 and in the sixth/seventh decades of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present case, the lesion was irregular and 7×5 cm in diameter with superficial hyperemia, clinically thought to be malignant. The lesions larger than 5 cm are generally defined as giant PMs [7]. To our knowledge, the largest reported PM in the literature was 24 cm in size and located in the upper back [8].…”
Section: Discussionmentioning
confidence: 95%
“…Most pilomatricomas are solitary, firm, mobile, blue to red appearing, dermally based masses less than 1 cm in diameter, with giant tumours (diameter > 5 cm) reported infrequently in the literature (Kovacic et al, 2007;Lozzi et al, 2007;Piel et al, 2009). While generally benign lesions, pain and inflammation at the tumour site can heighten clinical suspicion for malignancy, and malignant transformation has been reported (Sasaki et al, 1976;Phyu and Bradley, 2001).…”
Section: Introductionmentioning
confidence: 93%